Antioxidants in ripe peel and pulp of twelve mango (Mangifera indica) cultivars - MURALIDHARA, B M; VEENA, G L; BHATTACHERJEE, A K; RAJAN, S (The Indian Journal of Agricultural Sciences, 2019)
Mangoes are nutritionally rich subtropical fruits with unique flavour, fragrance, taste and health promoting compounds, making it one among new functional foods. Both peel and pulp contain many bioactive phytochemicals like phenolics, carotenoids, flavonoids, etc., which are proven antioxidants. The present study was carried out to profile these bioactive nutraceuticals in peel and pulp of 12 mango cultivars along with total antioxidant activity and L, a, and b values to identify the most beneficial health promoting cultivars. Total phenolics were estimated using Folin-Ciocalteu reagent, total flavonoids and total carotenoids by spectrophotometric methods and total antioxidant activity by CUPRAC (cupric reducing antioxidant capacity) assay. Colorimetric (L, a, and b) values were taken in a colorimeter. The data indicated significant variations in the contents of all three major phytochemicals in both peel and pulp of mango cultivars, where peel contained more nutraceuticals than pulp. The variation in total antioxidant activity in peel and pulp was also significant among the cultivars. It was noticed that total phenolics and total flavonoids contributed more towards total antioxidant activity as compared to total carotenoids. On the basis of the contents of total phenolics and total flavonoids along with total antioxidant activity, Neelum was found nutritionally richest cultivar followed by Mallika and Amrapali. Being rich in antioxidant principles, ripe mango peel can also be utilised for phenolics extraction through waste management technique and in phyto-pharmaceutical industry.